Plants used to treat hyperpigmentation in Iranian traditional medicine: a review - S. Ghafari; Sh. Fahimi; Sh. Sahranavard (Iranian Society of Pharmacognosy, 2017)
Skin hyperpigmentation is characterized as increased production and accumulation of melanin, which could be aesthetically unfavorable and develops serious skin diseases. There is a need to find new depigmenting agents, since many current natural and synthetic products present undesired side effects. In Iranian traditional medicine (ITM), plants have been used for the treatment of skin diseases such as hyperpigmentation. In this study, topical herbal medicines, for the treatment of hyperpigmentation were searched in ITM references, and their scientific names were identified, using different comprehensive glossaries. Thereafter, depigmenting mechanisms of these genera were reviewed in recent scientific literatures. Seventy-nine plants were made known as herbal remedies for skin hyperpigmentation. Furthermore, modern literatures have shown depigmenting effect of about 40% of these plants or their isolated compounds, with different melanogenesis inhibitory mechanisms with tyrosinase inhibition as the most revealed method. Regarding the new approach to medicinal plants in recent years, a large number of medicinal herbs that were mentioned in ITM references would be good candidates for exploring new herbal medicines for skin hyperpigmentation disorders.